Analysis of interaction between dislocation and interface of aluminum matrix/second phase from electronic behavior. (10th February 2023) - Yin, Qianxing; Chen, Guoqing; Shu, Xi; Zhang, Binggang; Li, Chun; Dong, Zhibo; Cao, Jian; An, Rong; Huang, Yongxian
Highlights: Difficulty in dislocation movement at interface is studied by electron transport. Change in valence electrons density at α-Al/second phase interface is calculated. Differential charge density at α-Al/second phase interfaces is analyzed. Inhibitory effect of α-Al/second phase interface on dislocation were studied. Abstract: The inhibitory effect of the second phase on dislocation movement has long been deemed as a great contribution to the strengthening of alloys. We investigate the electronic behavior at the α-Al matrix/second phase interface to explore its inhibitory effect on dislocation movement. This work focuses on the difficulty in dislocation movement on the interface of α-Al/Al3 Sc, α-Al/θ'(Al2 Cu), and α-Al/T1 (Al2 CuLi) of aluminum-lithium-scandium alloy based on detailed transmission electron microscopy investigation and electron transport calculation. The more drastic the electron transport between two atoms at the interface, the more intense the interaction between them, corresponding to the larger difficulty in breaking and forming bonds between them during the movement process of the extra half plane of dislocation on the interface. The calculated difference in density of valence electrons and differential charge density at α-Al/second phase interface reveals that Al3 Sc is characterized by the largest resistance to dislocation movement compared to θ'(Al2 Cu) and T1 (Al2 CuLi). The large differential charge density between the interface of (1 0 0)Al3Sc /(1 0 0)Al demonstrates the strong bonds between α-Al and Al3 Sc and the large difficulty for the extra half plane of dislocation to form or break bonds during the movement process at α-Al/Al3 Sc interface. The dislocation pile-up indicates a discernible hindering effect of the α-Al/Al3 Sc interface on dislocation movement. The hindering effect presented by α-Al/Al3 Sc interface is favorable for the tensile strength. Graphical abstract: Image, graphical abstract